COVID-19 Pandemic: Disparate Health Impact on the Hispanic/Latinx Population in the United States. (30th July 2020) - Macias Gil, Raul; Marcelin, Jasmine R; Zuniga-Blanco, Brenda; Marquez, Carina; Mathew, Trini; Piggott, Damani A
Abstract: In December 2019, a novel coronavirus known as SARS-CoV-2, emerged in Wuhan, China, causing the coronavirus disease 2019 we now refer to as COVID-19. The World Health Organization declared COVID-19 a pandemic on 12 March 2020. In the United States, the COVID-19 pandemic has exposed preexisting social and health disparities among several historically vulnerable populations, with stark differences in the proportion of minority individuals diagnosed with and dying from COVID-19. In this article we will describe the emerging disproportionate impact of COVID-19 on the Hispanic/Latinx (henceforth: Hispanic or Latinx) community in the United States, discuss potential antecedents, and consider strategies to address the disparate impact of COVID-19 on this population. Abstract : The COVID-19 pandemic has unveiled longstanding social and health disparities in the Hispanic/Latinx community in the United States. A multitiered approach will be critical to reduce the disproportionate impact of COVID-19 on the health and survival of the Hispanic/Latinx population.